Dietary and Nutritional Practices among Jordanian Patients with Type 1 and Type 2 Diabetes - Besher Gharaibeh (Jordan University of Science and Technology, 2023)
Background: assessment of dietary practices for patients with diabetes is essential and should be conducted in an iterative process. Aim: the aim of this study is to assess the dietary practices of Jordanian patients with type 1 and type 2 diabetes; and to assess the effect of the sociodemographic characteristic on these practices. Method: a cross sectional descriptive study was done using a sample of 310 participants. Data regarding the dietary practices were collected using items that were selected from the literature based on literature consensus and empirical works. Results: major proportion did not seek or attend sufficient training (n=181; 60%). None of the participants reported doing the right practice all the time, and sizable percent scored the lowest possible scores on the dietary practices in question, indicating doing the wrong practices frequently. Regression analysis showed that level of education positively impacted those practices. Females, younger patients, and those use traditional therapy tend to do the wrong dietary practices more frequently than their counterparts. Type of therapy used and type of diabetes had no effect on the dietary practices. Conclusion: Patients should be encouraged to seek proper diabetes training, as this training may boost their adherence to do the right dietary practices. Addressing dietary and nutritional behaviors might be beneficial over measuring a global adherence score because patient’s practices may vary over time. Implications to Nursing: Nurses should repetitively assess dietary practices as these practices might not be consistent over time. Further research is needed to clarify the effects on dietary practices.